2018
DOI: 10.17576/jsm-2018-4711-22
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nerve Conduit using Decellularized Human Umbilical Cord Artery Seeded with Centella asiatica Induced-Neurodiferrentiated Human Mesenchymal Stem Cell

Abstract: Various natural biological conduits have been investigated to bridge peripheral nerve injury especially in critical gap (greater than 3 cm in human). Autograft, the current gold standard, has several drawbacks including limited availability of donor graft, donor-site morbidity and mismatch in size in clinical practices. The aim of this study was to analyze the development of nerve conduit using decellularized human umbilical cord (HUC) artery seeded with neurodifferentiated human MSCs (ndMSCs) in bridging peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…H&E staining after the 2-day incubation of the seeded conduits showed that MSCs or ndMSCs were successfully seeded into the decellularized HUC artery conduit. The seeded cells, MSCs or ndMSCs, adhered, spread well in the inner wall of the decellularized artery conduit (Data not shown) and did not clump or aggregate, same as in our previous study [16]. These results showed the biocompatibility between the HUC artery conduit and the seeded cells.…”
Section: Development Of Nerve Conduitsupporting
confidence: 87%
See 3 more Smart Citations
“…H&E staining after the 2-day incubation of the seeded conduits showed that MSCs or ndMSCs were successfully seeded into the decellularized HUC artery conduit. The seeded cells, MSCs or ndMSCs, adhered, spread well in the inner wall of the decellularized artery conduit (Data not shown) and did not clump or aggregate, same as in our previous study [16]. These results showed the biocompatibility between the HUC artery conduit and the seeded cells.…”
Section: Development Of Nerve Conduitsupporting
confidence: 87%
“…Following our success in constructing a nerve conduit by using HUC artery seeded with C. asiatica ndMSCs [16], this conduit was further tested by bridging PNI in rats and utilising this nerve graft. Given the 12 weeks of recovery period, the study on a 15 mm transectional sciatic nerve injury in SD rat model revealed that (1) the HUC artery Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of PNS, particularly in the crucial gap of more than 3 cm, remains a significant clinical issue despite the tremendous advancements in medicine ( Hussin et al, 2018 ). According to reports, many variables, such as the extent of the injury, the presence of neurotrophic factors, the existence of Schwann cells, etc., affect the restricted regeneration of peripheral nerves.…”
Section: Nerve Repair With Tissue Engineering Scaffoldsmentioning
confidence: 99%